Criopreservación de embriones de trucha arcoiris (Oncorhynchus mykiss) en el laboratorio de biotecnología de la reproducción de la carrera de medicina veterinaria de la Universidad Técnica de Cotopaxi - Anchacaisa Velasco, Darwin Omar (2015)
The following research was conducted in order to evaluate the cryopreservation of Rainbow Trout embryos, for this research was applied a protocol based on 1.5 M ethylene and 0.1 M of saccharose as cryoprotectants, ViGROR Ethylene Glycol Freeze Plus with Sucrose. Embryos with quality A in a blastocyst stage after eight hours post fertilization were used and subsequently we evaluate the morphology post thawing presented, then the procedure of categorization according to the results was performed. It was applied non experimental investigation with descriptive statistics to describe the protocol without altering variables. Two females and two males from Rainbow Trout specie were used, after that, the trout eggs were fertilized and finally, these were classified in order to use the fertilized eggs with quality “A” to keep a complete and intact structure. Eight hours after, the fertilized eggs were classified according to the structure, using quality “A” eggs, then the selected embryos were maintained on a thermal iron with a temperature of 23 °C in a Holding maintenance solution....